Lanthanum nickelate ceramic target material and preparation method thereof
By using a specific proportion of N I2O3 and LA2O3 powder, combined with wet method mixed powder and hot sintering technology to prepare nickel -pyrotinate ceramic targets, solve the problem of difficulty guarantee the quality of target materials in existing technology, and achieve high density, uniformity, uniformity, uniformity Targets of sex and excellent sputtering performance.
Patent Information
- Application Number
- CN202411469746.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The method of preparing lanthanum nitriate ceramic targets in the prior art is complex, difficult to control, and easy to introduce impurities, resulting in the inability to guarantee the quality of the target.
Ni2O3 powder and La2O3 powder with a mass ratio of 2:(3-8) are used as raw materials, and the lanthanum nickelate ceramic target is prepared through wet mixing, pre-synthesis, molding, pre-pressing, hot-pressing sintering and other steps to ensure High purity and uniformity.
The density and quality of the nickel -nickel -mandarin ceramic target is improved, the flatness and sputtering performance of the target are ensured, and the uniformity of the target and the consistency of the batch of products is significantly improved.
Smart Images

Figure CN119350025A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lanthanum nickelate ceramic target materials, and in particular to a lanthanum nickelate ceramic target material and a preparation method thereof. Background Art
[0002] Usually, the material used as the bottom electrode of ferroelectric thin film devices is mainly the precious metal platinum (Pt). Platinum has good electrical conductivity, but the preparation cost is extremely high, and the adhesion and fatigue resistance of ferroelectric thin films on platinum are both insufficient. However, the metal oxide lanthanum nickelate (LaN i O3) with a perovskite structure has good electrical conductivity and low cost, and is an excellent material for the bottom electrode of ferroelectric thin films. Because the target material has a great influence on the performance of the sputtered film, and the higher the purity of the ceramic target material, the better the uniformity of the sputtered film and the consistency of the quality of the batch product, the prerequisite for preparing high-quality lanthanum nickelate thin films is to prepare high-quality lanthanum nickelate ceramic targets.
[0003] In the prior art, the technology for preparing lanthanum nickelate ceramic targets is relatively simple. For example, the patent document with publication number CN103664170A discloses a technology for preparing lanthanum nickelate ceramic targets, which pre-synthesizes lanthanum nickelate ceramic powder by solid phase reaction, and then obtains a green body by pressing at room temperature, and obtains a lanthanum nickelate target after pressureless sintering of the green body. However, the preparation process of this method is relatively complicated, there are many uncontrollable factors, and other impurities are easily introduced, and the quality of the obtained lanthanum nickelate ceramic target cannot be guaranteed. Summary of the invention
[0004] The purpose of the present invention is to provide a lanthanum nickelate ceramic target and a preparation method thereof to solve the following technical problems:
[0005] How to improve the quality of lanthanum nickel oxide ceramic targets.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] In the first aspect, the present invention discloses a lanthanum nickelate ceramic target, characterized in that its raw material components include Ni2O3 powder and La2O3 powder in a mass ratio of 2:(3-8), and the density of the lanthanum nickelate ceramic target is ≥4g / cm 3 .
[0008] In a further embodiment of the present invention, the purity of the Ni2O3 powder and the La2O3 powder are both greater than 99.999%.
[0009] In a further embodiment of the present invention: the average median diameter of the Ni2O3 powder is 10-15 um, and the average median diameter of the La2O3 powder is 20-25 um;
[0010] Preferably, the average median diameter of the Ni2O3 powder is 10 um;
[0011] Preferably, the average median diameter of La2O3 powder is 20 um.
[0012] In a second aspect, the present invention further discloses a method for preparing the lanthanum nickelate ceramic target as described above, comprising the following steps:
[0013] S1. Wet mixing
[0014] Weigh Ni2O3 powder and La2O3 powder, mix and grind them by wet method to obtain mixed powder.
[0015] S2:L i N i O X Ceramic powder synthesis
[0016] The mixed powder is placed in a synthesis furnace for pre-synthesis, oxygen is introduced at 400-600°C, the synthesis temperature is 800-1000°C, and the heat preservation time is 5-10h. After the synthesis is completed, LiniO X Ceramic powder;
[0017] Preferably, the temperature of the oxygen is 500°C;
[0018] Preferably, the synthesis temperature is 900° C. and the holding time is 8 h.
[0019] S3: Mold Installation
[0020] Cut the graphite paper according to the size of the mold, place the graphite paper on the bottom and inner side of the mold, and then place the LiniO X The ceramic powder is spread in the mold and leveled.
[0021] S4: Preload
[0022] Place the graphite mold containing the mixed powder in a vacuum hot pressing sintering furnace and increase the pressure to 6-10MPa, then maintain the pressure for 10-15 minutes and release the pressure to zero;
[0023] Preferably, the pressure is increased to 8 MPa and kept warm for 12 hours.
[0024] S5: Hot Pressing Sintering
[0025] After the vacuum is evacuated to below 5Pa, the temperature is raised to 600-800℃ at a heating rate of 8-10℃ / min, and then the heating rate is adjusted to 5-8℃ / min and the temperature is raised to 900-1100℃, and the temperature is kept for 30-60min; after the heat preservation is completed, the pressure is increased to 20-25MPa at a pressure rate of 0.1-0.3MPa / min, and the temperature is kept for 90-150min, and finally the temperature is lowered to 100-200℃ with the furnace, and LiniO is obtained after the end. X Ceramic target blank;
[0026] S6: Machining
[0027] RemoveL i N i O X The graphite paper on the ceramic target blank is grinded and CNC processed according to the requirements of the drawings, and machined into a target material of qualified size. Relevant defects and density tests are carried out, and vacuum packaging is carried out if no abnormalities are found.
[0028] Preferably, the temperature is raised to 700°C at a heating rate of 9°C / min, and then the heating rate is adjusted to 7°C / min and the temperature is raised to 1000°C, and the temperature is kept for 45 minutes;
[0029] Preferably, after the heat preservation is completed, the pressure is increased to 23 MPa at a pressurization rate of 0.2 MPa / min, and the heat and pressure are maintained for 120 minutes, and finally the temperature is lowered to 150° C. with the furnace.
[0030] In a further embodiment of the present invention, in step S1, the wet mixing and grinding method comprises the following steps:
[0031] Pour the weighed Ni2O3 powder and La2O3 powder into the polyurethane mixing barrel, add the mixing balls, then add anhydrous ethanol, and then use a drum ball mill to mix at a speed of 300-400r / min for 20-32h;
[0032] Preferably, the mixture is mixed in a drum mill at a speed of 350 r / min for 25 h.
[0033] In a further embodiment of the present invention, the mixed powder balls are added at a ball-to-material ratio of 1:2.
[0034] In a further embodiment of the present invention, the powder mixing ball is one of a polyurethane grinding ball, an agate grinding ball or a zirconium oxide grinding ball.
[0035] In a further embodiment of the present invention: the amount of anhydrous ethanol added is 20%-30% of the sum of the weight of Ni2O3 powder and La2O3 powder;
[0036] Preferably, the amount of anhydrous ethanol added is 25% of the sum of the weight of Ni2O3 powder and La2O3 powder.
[0037] In a further embodiment of the present invention: in step S3, the mold is a high-purity graphite mold.
[0038] In a further embodiment of the present invention: in step S4, the pressure is increased to 6-10 MPa at a pressure increase rate of 0.1-0.3 MPa / min;
[0039] Preferably, the pressure is increased to 8 MPa at a pressure increasing rate of 0.2 MPa / min.
[0040] Beneficial effects of the present invention:
[0041] The lanthanum nickelate ceramic target material of the present invention is obtained by directly hot-pressing and sintering the lanthanum nickelate ceramic powder after solid phase synthesis at low temperature and high pressure, and supplementing the pressure is performed during the heat preservation stage of 600-800° C. during the sintering stage to avoid radial shrinkage. After reaching the sintering temperature, while the temperature field is uniform, a lower pressurization rate is used to effectively avoid cracking of the target material, so that the grain structure is uniform and fine, and the lanthanum nickelate ceramic powder finally obtained has a very flat flatness, high density and excellent sputtering performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The present invention will be further described below in conjunction with the accompanying drawings.
[0043] Figure 1 It is a flow chart of the preparation method of the lanthanum nickelate ceramic target material of the present invention. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0046] Example 1
[0047] 100g Ni2O3 powder (purity>99.999%, average median diameter 10um) and 400g La2O3 powder (purity>99.999%, average median diameter 20um) were weighed and added into a 10L polyurethane powder mixing barrel, 250g zirconium oxide grinding balls were added, and then 100g anhydrous ethanol was added. The speed of the drum ball mill was set to 300r / min, and the mixture was mixed at the speed for 32h to obtain a mixed powder. The mixed powder was placed in a synthesis furnace, oxygen was introduced at 400°C, and then the temperature was raised to 800°C and kept warm for 10h. After the end, LiNiO x Ceramic powder; select a high-purity graphite mold and cut the graphite paper according to its size, place the graphite paper on the bottom and inner side of the mold, and then XThe ceramic powder is spread flat in a graphite mold; the graphite mold containing the mixed powder is placed in a vacuum hot pressing sintering furnace, the pressure is increased to 6MPa at a pressure increase rate of 0.1MPa / min, and then the pressure is released to zero after the pressure is maintained for 15min, and then the temperature is increased after the vacuum is evacuated to below 3Pa, and the temperature is increased to 600℃ at a heating rate of 8℃ / min, and then the heating rate is adjusted to 5℃ / min and the temperature is increased to 900℃, and the temperature is maintained for 60min; after the insulation is completed, the pressure is increased to 20MPa at a pressure increase rate of 0.1MPa / min, and the temperature is maintained for 150min, and finally the temperature is reduced to 100℃ with the furnace, and LiniO is obtained after the end. X Ceramic target blank.
[0048] Example 2
[0049] 100 g Ni2O3 powder (purity> 99.999%, average median diameter 10 μm) and 250 g La2O3 powder (purity> 99.999%, average median diameter 20 μm) were weighed and added into a 10 L polyurethane powder mixing barrel, 175 g zirconium oxide grinding balls were added, and then 87.5 g anhydrous ethanol was added. The speed of the drum ball mill was set to 350 r / min, and the mixture was mixed at the speed for 25 h to obtain a mixed powder. The mixed powder was placed in a synthesis furnace, oxygen was introduced at 500 ° C, and then the temperature was raised to 900 ° C and kept warm for 8 h. After the end, LiniO x Ceramic powder; select a high-purity graphite mold and cut graphite paper according to its size, place the graphite paper on the bottom and inner side of the mold, and then X The ceramic powder is spread flat in a graphite mold; the graphite mold containing the mixed powder is placed in a vacuum hot pressing sintering furnace, the pressure is increased to 8MPa at a pressure increase rate of 0.2MPa / min, and then the pressure is released to zero after the pressure is maintained for 12min, and then the temperature is increased after the vacuum is evacuated to 5Pa, and the temperature is increased to 700℃ at a heating rate of 9℃ / min, and then the heating rate is adjusted to 7℃ / min and the temperature is increased to 1000℃, and the temperature is maintained for 45min; after the insulation is completed, the pressure is increased to 23MPa at a pressure increase rate of 0.2MPa / min, and the temperature is maintained for 120min, and finally the temperature is reduced to 150℃ with the furnace, and LiniNiO is obtained after the end. X Ceramic target blank.
[0050] Example 3
[0051] 100g Ni2O3 powder (purity>99.999%, average median diameter 10um) and 150g La2O3 powder (purity>99.999%, average median diameter 20um) were weighed and added into a 10L polyurethane powder mixing barrel, 125g zirconium oxide grinding balls were added, and then 75g anhydrous ethanol was added. The speed of the drum ball mill was set to 400r / min, and the mixture was mixed at the speed for 20h to obtain a mixed powder. The mixed powder was placed in a synthesis furnace, oxygen was introduced at 600°C, and then the temperature was raised to 1000°C and kept warm for 5h. After the end, LiNiO x Ceramic powder; select a high-purity graphite mold and cut the graphite paper according to its size, place the graphite paper on the bottom and inner side of the mold, and then X The ceramic powder is spread flat in a graphite mold; the graphite mold containing the mixed powder is placed in a vacuum hot pressing sintering furnace, the pressure is increased to 10 MPa at a pressure increase rate of 0.3 MPa / min, and then the pressure is released to zero after the pressure is maintained for 10 minutes, and then the temperature is increased after the vacuum is evacuated to 4 Pa, and the temperature is increased to 800°C at a heating rate of 10°C / min, and then the heating rate is adjusted to 8°C / min and the temperature is increased to 1100°C, and the temperature is maintained for 30 minutes; after the insulation is completed, the pressure is increased to 25 MPa at a pressure increase rate of 0.3 MPa / min, and the temperature is maintained for 90 minutes, and finally the temperature is reduced to 200°C with the furnace, and LiniO is obtained after the end. X Ceramic target blank.
[0052] Comparative Example 1
[0053] 100 g Ni2O3 powder (purity> 99.999%, average median diameter 10 μm) and 250 g La2O3 powder (purity> 99.999%, average median diameter 20 μm) were weighed and added into a 10 L polyurethane powder mixing barrel, 175 g zirconium oxide grinding balls were added, and then 87.5 g anhydrous ethanol was added. The speed of the drum ball mill was set to 350 r / min, and the mixture was mixed at the speed for 25 h to obtain a mixed powder. The mixed powder was placed in a synthesis furnace, oxygen was introduced at 500 ° C, and then the temperature was raised to 900 ° C and kept warm for 8 h. After the end, LiniO x Ceramic powder; select a high-purity graphite mold and cut graphite paper according to its size, place the graphite paper on the bottom and inner side of the mold, and then XThe ceramic powder is spread flat in a graphite mold; the graphite mold containing the mixed powder is placed in a vacuum hot pressing sintering furnace, the pressure is increased to 8 MPa at a pressure increase rate of 0.2 MPa / min, and then the pressure is released to zero after maintaining the pressure for 12 minutes, and then the temperature is increased after vacuuming to 5 Pa, and the temperature is increased to 700°C at a heating rate of 9°C / min, and then the heating rate is adjusted to 7°C / min and the temperature is increased to 1000°C, and the temperature is maintained for 45 minutes, and finally the temperature is reduced to 150°C with the furnace, and LiNiO is obtained after the end. X Ceramic target blank.
[0054] Comparative Example 2
[0055] Compared with Example 2, the only difference is that "the temperature is raised after vacuuming to 5Pa" is adjusted to "the temperature is raised after vacuuming to 6Pa", and other conditions remain the same, and finally LiniO X Ceramic target blank.
[0056] The LiniO prepared in Examples 1-3 and Comparative Examples 1-2 X Ceramic target material is tested for performance, including grain distribution uniformity and density. In order to facilitate testing, LiniO X The ceramic target blank is machined into a square shape with a length, width and height of 3 cm by a grinder and CNC processing. The specific detection method is as follows.
[0057] Grain distribution uniformity detection: Use a digital multimeter as the resistance detection element, and X Several horizontal detection points and several vertical detection points are set in the middle of the ceramic target, and the test pens of the resistance detection instrument are connected to the LiniO X A closed circuit is formed at each detection point of the ceramic target, and the resistance value of each detection point is measured and recorded in turn. The smaller the difference in resistance value, the higher the uniformity of grain distribution of the target, and vice versa. The data difference is reflected by calculating the variance of the corresponding resistance of the horizontal detection point and the vertical detection point respectively.
[0058] Density detection: Calculate the target density by weighing method.
[0059] The test results are listed in Table 1. Table 1 is as follows:
[0060] Table 1
[0061]
[0062] By analyzing the data in Table 1, it can be seen that the LiniO prepared in Examples 1-3 X The ceramic target is compared with the LiniO prepared in Comparative Example 1-2.X Compared with ceramics, its grain distribution uniformity and density are significantly higher, which shows that the LiniNiO X Ceramic targets are of better quality.
[0063] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A lanthanum nickelate ceramic target, characterized in that: The raw material components include Ni2O3 powder and La2O3 powder in a mass ratio of 2:(3-8), and the density of the nickel oxide lanthanum ceramic target is ≥4g / cm 3 .
2. The lanthanum nickelate ceramic target according to claim 1, characterized in that: The purity of the Ni2O3 powder and the La2O3 powder are both greater than 99.999%.
3. The lanthanum nickelate ceramic target according to claim 2, characterized in that: The average median diameter of the Ni2O3 powder is 10-15um, and the average median diameter of the La2O3 powder is 20-25um.
4. A method for preparing a lanthanum nickelate ceramic target according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Wet mixing Weigh Ni2O3 powder and La2O3 powder and mix and grind them by wet method to obtain mixed powder; S2: LiNiO X Ceramic powder synthesis The mixed powder is placed in a synthesis furnace for pre-synthesis, oxygen is introduced at 400-600°C, the synthesis temperature is 800-1000°C, and the insulation time is 5-10h. After the synthesis is completed, LiNiO is obtained. X Ceramic powder; S3: Mold Installation Cut the graphite paper according to the mold size, place the graphite paper on the bottom and inner side of the mold, and then X The ceramic powder is spread in the mold and leveled; S4: Preload Place the graphite mold containing the mixed powder in a vacuum hot pressing sintering furnace and increase the pressure to 6-10MPa, then maintain the pressure for 10-15 minutes and release the pressure to zero; S5: Hot Pressing Sintering After the vacuum is evacuated to below 5Pa, the temperature is raised to 600-800℃ at a heating rate of 8-10℃ / min, and then the heating rate is adjusted to 5-8℃ / min and the temperature is raised to 900-1100℃, and the temperature is kept for 30-60min; after the heat preservation is completed, the pressure is increased to 20-25MPa at a pressure rate of 0.1-0.3MPa / min, and the temperature is kept for 90-150min, and finally the temperature is lowered to 100-200℃ with the furnace, and LiNiO is obtained after the end. X Ceramic target blank; S6: Machining Removal of LiNiO X The graphite paper on the ceramic target blank is grinded and CNC processed according to the drawing requirements, and the target material with qualified size is machined. The relevant defects and density tests are carried out. If there is no abnormality, vacuum packaging is obtained to obtain LiNiO X Ceramic targets.
5. The method for preparing the lanthanum nickelate ceramic target according to claim 4, characterized in that: In step S1, the wet mixing and grinding method comprises the following steps: Pour the weighed Ni2O3 powder and La2O3 powder into the polyurethane mixing barrel, add the mixing powder balls, then add anhydrous ethanol, and then use a drum ball mill to mix at a speed of 300-400r / min for 20-32h.
6. The method for preparing the lanthanum nickelate ceramic target according to claim 5, characterized in that: The mixed powder balls are added at a ball-to-material ratio of 1:
2.
7. The method for preparing a lanthanum nickelate ceramic target according to claim 5, characterized in that: The powder mixing ball is one of a polyurethane grinding ball, an agate grinding ball or a zirconium oxide grinding ball.
8. The method for preparing a lanthanum nickelate ceramic target according to claim 5, characterized in that: The added amount of the anhydrous ethanol is 20%-30% of the total weight of the Ni2O3 powder and the La2O3 powder.
9. The method for preparing a lanthanum nickelate ceramic target according to claim 4, characterized in that: In step S3, the mold is a high-purity graphite mold.
10. The method for preparing a lanthanum nickelate ceramic target according to claim 4, characterized in that: In step S4, the pressure is increased to 6-10 MPa at a pressure increase rate of 0.1-0.3 MPa / min.
Citation Information
Patent Citations
Method for preparing lanthanum nickelate conductive metallic oxide nano-film
CN101343729A
Preparation technology of lanthanum nickelate ceramic target
CN103664170A
Lanthanum nickel oxide conductive film and preparation method and application thereof
CN108511112A
Piezoelectric element and method for manufacturing the same, ink jet recording head and ink jet printer
US20060213043A1
Cited By
B-site doped medium-entropy lanthanum nickelate ceramic spraying powder and preparation method thereof
CN120025169A